ANALISIS KREDIT BERMASALAH DAN PENYALURAN KREDIT DALAM UPAYA MENINGKATKAN PENDAPATAN PERUSAHAAN - Hasna, Ishfa Naqiyyan; Suherman, Acep; Indrawan, Andri (LPPM Universitas Bina Bangsa, 2024)
Non-performing loans are the biggest risk that can lead to the liquidation of a bank. Non-performing loans are something that can affect the continuity of bank operations, because they can cause losses and do not accumulate interest and other income, thus disrupting bank operations, especially in terms of liquidity adequacy. The type of research used by the author is a qualitative descriptive method, the data processed is data obtained from the results of interviews and unstructured observations that will be analyzed qualitatively and described in descriptive form. Non-performing loans (NPL) are one of the main risks faced by PT BPR Supra Artapersada KC Sukabumi. Although the company has implemented strict procedures in credit distribution based on the 5C principle (Character, Capacity, Capital, Collateral, Condition), various internal and external factors still affect the NPL level. BPR Supra has implemented the 5C principle in the credit distribution process, it is advisable to update and tighten the credit evaluation criteria periodically, especially in the face of uncertain economic conditions